An innovative method for the fractionation and pretreatment of pig farm biogas slurry by ultrafiltration. (August 2022) - Zeng, Weishen; Lu, Riming; Wang, Dehan; He, Lintong; Wu, Zhaoyun
Abstract: Humic acids and macromolecular organics in pig farm wastewater can limit the efficacy of biochemical treatment and lead to high chroma. In this work, an ultrafiltration (UF) pretreatment method for building pig farm wastewater was developed. Key process parameters, such as the membrane molecular weight cutoff (MWCO), transmembrane pressure (TMP) and permeate reflux ratio, were explored and optimized. The membrane fouling was evaluated, and the UF permeate underwent sequencing batch reactor (SBR) biochemical treatment. The UF performance was appropriate at 100 kDa and 0.1 MPa. When the permeate reflux ratio was 200%, the UF time was shortened by half. After the UF permeate underwent SBR biochemical treatments, the effluent met the current discharge standards (GB18596-2001). The gas chromatography–mass spectrometry (GC–MS) results showed that UF pretreatment can reduce the concentration and types of organics in the SBR effluent. A new wastewater treatment and resource recovery method for building pig farms is provided. Graphical abstract: Unlabelled Image Highlights: SF/UF can retain 20% macromolecular organics and reduce 52% of the COD in biogas slurry. When the permeate reflux ratio is 200%, the UF time can be shortened by half. UF pretreatment can reduce the types and concentrations of organics in SBR effluent.